Information by healthcare professionals for decision-making of Type 2 Diabetes Mellitus management in Malaysia: comparison with shared decision-making model - Atan, Ashikin; Rhynas, Sarah; Fawcet, Tonks; Lee, Siew Pien; Wan Mamat, Wan Hasliza; Ahmad, Norfadzilah (2022)
Background: Relevant and sufficient information exchange between patients and healthcare professionals (HCPs) is imperative in the concept of shared decision-making. This concept is gaining attention as the patients are more satisfied with the decision and significant improvement in their health condition can also be seen. Objective: This paper aims to present the perceptions and experiences of patients and the HCPs on the information provided by the HCPs related decision-making in managing Type 2 Diabetes Mellitus (T2DM) in Malaysia. Further comparison of the gathered data was done against the shared decision-making model. Methods: Using an exploratory qualitative design, the perception of T2DM patients and the HCPs of three outpatient settings in the urban area of Malaysia were explored. Face-to-face in-depth interviews were conducted, over a period of six months, with 24 T2DM patients and 19 HCPs. Thematic analysis was used to analyse the data interpretively. Results: The following three important themes were emerged and discussed in this paper: (1) HCPs are giving instructions; (2) Other options are offered if necessary; (3) Insufficient information. Conclusion: Overall, the findings indicate that the practice of information provision in decision-making is still lacking among HCPs.